Hubungan Career Adaptability dengan Hardiness Mahasiswa Tingkat Akhir Kependidikan Universitas Negeri Padang - Anjelika, Tiara; Kurniawan, Rizal (TSAQOFAH, 2024)
This research aims to determine the relationship between career adaptability and hardiness of final year education students at Padang State University. This study uses quantitative methods with a correlational quantitative method design. Data collection techniques using proportionated stratified random sampling. The sample in this study amounted to 375 respondents. This research instrument uses The Career Adapt-Abilities Scale Indonesian Form scale from Sulistiani et al., (2019) and a hardiness scale based on the theory of Kobasa., et al (1982). The results of the analysis used product moment correlation and found that there was a significant relationship between career adaptability and hardiness of final year education students at Padang State University.